ANALISIS KARAKTERISTIK LITERATUR YANG DISITIR DALAM ARTIKEL JURNAL ILMIAH INDONESIA - Marlina, Ekawati; Kusumaningrum, Dwiatri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
Journal publication is a tool that is widely used by scientists to disseminate their work. Scientists need reference sources to support the result of his research. Literature cited to support his writing are then listed as reference. ISJD is the Indonesian journal indexer containing more than 250,000 articles. Out of those 250,000 articles, how many articles cite other articles from Indonesian journals. Citation is a form of scientific communication among scientists. This study was aimed at finding out how Indonesian scientists communicate one another through journal publication. Another objective was to find out the types of literature cited in the study. Samples were taken from the ISJD database in health sciences. From the analysis, it was found that articles cite other articles from Indonesian journals comparatively low, only 7,7%. The use of citations of Indonesian Scientific journal published by foreign is the most widely cited literature followed by Indonesian books, foreign books, Indonesian journals, newspaper/ web articles, Indonesian dissertations/ theses, Indonesian proceedings, Indonesian undergraduate thesis, Indonesian reports research/ technical reports, foreign proceedings, Indonesian Law, foreign research reports / technical reports, and foreign dissertations/ theses. Beside the type of literature, literatur was also distinguished by the publisher (Indonesian and foreign). The most frequently cited literature was journal that published by foreign. The second was Indonesian books, than foreign books, Indonesian journals, newspaper articles/ web articles, Indonesian dissertations/theses, Indonesian proceedings, Indonesian undergraduate thesis, Indonesian reports research / technical reports, foreign proceedings, Indonesian Law, foreign research reports/ technical reports, and foreign dissertations/ theses.